2017
DOI: 10.1088/1361-648x/aa76be
|View full text |Cite
|
Sign up to set email alerts
|

Charge ordering and magnetic frustration in CsFe2F6

Abstract: The structural, electronic and magnetic properties of a charge-ordered iron fluoride material CsFeFeF have been explored by density functional theory calculations based on the generalized gradient approximation  +  U approach, which was implemented in the VASP code. The material exhibits a 3D pyrochlore-related structure which consists of corner-shared FeF and FeF octahedra. Our results confirm that CsFeF is a Mott-Hubbard insulator, and bears a magnetically frustrated ground state in which the localized 3d el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…15,33,40,41 Known orthorhombic charge-ordered CsFe 2+ Fe 3+ F 6 and RbFe 2+ Fe 3+ F 6 pyrochlores result in frustration indices of 19 and 17, respectively, which indicate low frustration compared to the disordered CsNiFeF 6 (f = 37) and CsCoFeF 6 (f = 54.5), even though their Weiss temperatures are closer to each other. 15,20,21 Cubic to orthorhombic structure changes can influence the less homogeneous exchange interactions between magnetic ions, which leads to a more ordered magnetic structure with fewer competing interactions and less frustration. This suggests that the frustration index is decreasing in going from the cubic pyrochlore to the orthorhombic pyrochlore to the inverse weberite and to the weberite structure.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,33,40,41 Known orthorhombic charge-ordered CsFe 2+ Fe 3+ F 6 and RbFe 2+ Fe 3+ F 6 pyrochlores result in frustration indices of 19 and 17, respectively, which indicate low frustration compared to the disordered CsNiFeF 6 (f = 37) and CsCoFeF 6 (f = 54.5), even though their Weiss temperatures are closer to each other. 15,20,21 Cubic to orthorhombic structure changes can influence the less homogeneous exchange interactions between magnetic ions, which leads to a more ordered magnetic structure with fewer competing interactions and less frustration. This suggests that the frustration index is decreasing in going from the cubic pyrochlore to the orthorhombic pyrochlore to the inverse weberite and to the weberite structure.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Previous studies have shown that orthorhombic pyrochlores, such as CsFeFeF 6 ( f = 19), RbFeFeF 6 ( f = 17), and CsMnMnF 6 ( f = 4), exhibit lower magnetic frustration compared to their cubic counterparts, including CsNiFeF 6 ( f = 37), CsCoFeF 6 ( f = 54), and CsMnFeF 6 ( f = 11). ,, Therefore, we are interested in studying β-pyrochlores having cubic symmetry in order to test their magnetic frustration. The cubic pyrochlore compositions reported in the literature were obtained using the flux method, and some of the orthorhombic charge-ordered pyrochlores were synthesized using both flux and mild hydrothermal methods. , Although cubic AM 2+ M 3+ F 6 pyrochlores (A = Cs and Rb; M 2+ = Co 2+ , Ni 2+ , and Mn 2+ ; and M 3+ = Fe 3+ and Cr 3+ ) have been studied for their magnetism, those with M 3+ = V 3+ remain unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of compounds with AM 2+ M 3+ F 6 composition, but only a few of them exhibit charge ordering and long-range magnetic ordering of the M sites. ,,, Among them is a series of isostructural iron compounds A Fe 2+ Fe 3+ F 6 ( A = NH 4 + , Rb + , Cs + ) that undergo a one-step antiferromagnetic transition at temperatures of 19, 16, and 13.7 K, respectively. ,,, Although only the magnetic structures of the NH 4 + and Rb + analogs have been reported, similar magnetization behavior of CsFe 2 F 6 suggests that it might have a similar magnetic structure. As in CsMn 2 F 6 , the nuclear and magnetic unit cell in NH 4 Fe 2 F 6 and RbFe 2 F 6 have identical metrics; however, the symmetry of the CsMn 2 F 6 magnetic unit cell after the first transition is different from the symmetry of the Fe-based analogs.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The moment on the Mn1 rapidly There are a number of compounds with AM 2+ M 3+ F 6 composition, but only a few of them exhibit charge ordering and long-range magnetic ordering of the M sites. [33][34][35]40,57,58 Among them is a series of isostructural iron compounds AFe 2+ Fe 3+ F 6 (A = NH 4 + , Rb + , Cs + ) that undergo a one-step antiferromagnetic transition at temperatures of 19, 16, and 13.7 K, respectively. 31,33,34,57 Although only the magnetic structures of the NH 4 + and Rb + analogs have been reported, similar magnetization behavior of CsFe 2 F 6 suggests that it might have a similar magnetic structure.…”
Section: T H Imentioning
confidence: 99%
“…These are often studied in 3D oxides with corner sharing tetrahedral lattices such as spinels 26 or pyrochlores 27 . Apart from oxides, the fluoride CsFe 2 F 6 28 pyrochlore and the In-diluted thiospinel CdCr 2x In 2(1−x) S 4 29 -30 are spinglass materials. In Bi 1.8 Fe 1.2 SbO 7 31 pyrochlore, anion mixing trough fluorination led to variation of the spin glass dynamics.…”
mentioning
confidence: 99%